A novel near-infrared fluorescent hydrogen sulfide probe for live cell and tissue imaging. (1st April 2019) - Huang, Xiaoting; Liu, Haiyang; Zhang, Jiewen; Xiao, Boren; Wu, Fengxu; Zhang, Yueying; Tan, Ying; Jiang, Yuyang
Abstract : A novel sensitive near-infrared fluorescence enhanced NIR-NP probe with a large Stokes shift for H2 S analysis was developed. Abstract : A dicyanoisophorone-based near-infrared fluorescent probe (NIR-NP) was successfully designed for hydrogen sulfide (H2 S) detection. 7-Nitro-1, 2, 3-benzoxadiazole (NBD) amine, an electron-withdrawing group, was applied to quench the fluorescence of dicyanoisophorone-based fluorescent dyes and could be removed by H2 S-specific thiolysis of an NBD amine bond, leading to a significant fluorescence turn-on response. The probe could quantitatively detect H2 S with a lower detection limit (0.03 μM) in vitro and in living cells. The probe with a large Stokes shift (186 nm) showed a high selectivity to H2 S in the presence of other biothiols, including glutathione, homocysteine, and cysteine. Moreover, the probe was successfully applied to image endogenous H2 S in different tumor cells and in liver tissues. The excellent properties of the probe and its applications in cell and tissue imaging indicated its potential for further exploration and application of H2 S in the pathophysiology of cancers and even in the diagnosis of H2 S-related diseases.